PHYTOCHEMICAL INVESTIGATION AND IN VITRO ANTIOXIDANT ACTIVITY OF ARGEMONE MAXICANA LINN - RAJINI SHRIVASTAVA; SHOWKET HUSSAIN BHAT; MOHD YOUSUF MALLA; MOHD YOUSUF MALLA; MOHD IQBAL MIR (International Journal of Pharma and Bio Sciences, 2013)
The present study was aimed to investigate the phytochemicals and antioxidant potential of crude extract of Argemone maxicana linn The Phytochemical screening showed the presence of alkaloids, flavonoids, tepinoids, carbohydrates, saponins and tannins. The antioxidant property of the extract was assessed by 2, 2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging method.